Methadone dose and neonatal abstinence syndrome-systematic review and meta-analysis. - Cleary, B; Donnelly, J; Strawbridge, J; Gallagher, P; Fahey, T; Clarke, M; Murphy, D (2010)
AIM: To determine if there is a relationship between maternal methadone dose in pregnancy and the diagnosis or medical treatment of neonatal abstinence syndrome (NAS). METHODS: PubMed, EMBASE, the Cochrane Library and PsychINFO were searched for studies reporting on methadone use in pregnancy and NAS (1966-2009). The relative risk (RR) of NAS was compared for methadone doses above versus below a range of cut-off points. Summary RRs and 95% confidence intervals (CI) were estimated using random effects meta-analysis. Sensitivity analyses explored the impact of limiting meta-analyses to prospective studies or studies using an objective scoring system to diagnose NAS. RESULTS: A total of 67 studies met inclusion criteria for the systematic review; 29 were included in the meta-analysis. Any differences in the incidence of NAS in infants of women on higher compared with lower doses were statistically non-significant in analyses restricted to prospective studies or to those using an objective scoring system to diagnose NAS. CONCLUSIONS: Severity of the neonatal abstinence syndrome does not appear to differ according to whether mothers are on high- or low-dose methadone maintenance therapy.